Intraventricular versus intravenous colistin for the treatment of extensively drug resistant Acinetobacter baumannii meningitis. (31st July 2015) - De Bonis, P.; Lofrese, G.; Scoppettuolo, G.; Spanu, T.; Cultrera, R.; Labonia, M.; Cavallo, M. A.; Mangiola, A.; Anile, C.; Pompucci, A.
Abstract : Background and purpose: Reports on the safety and efficacy of intraventricularly administered (IVT) colistin for the treatment of Acinetobacter baumannii ventriculomeningitis in adults are limited and no comparative studies of IVT colistin versus intravenous (IV) therapy alone have been published. This study compared outcomes of patients with postneurosurgical ventriculomeningitis caused by extensively drug‐resistant A. baumannii treated with IV colistin or IV plus IVT colistin. Methods: In an 11‐year period, information on 18 consecutive patients with extensively drug‐resistant A. baumannii ventriculomeningitis was collected. Infection was defined on the basis of (i) isolation of A. baumannii from the cerebrospinal fluid (CSF); (ii) laboratory evidence of CSF infection; (iii) signs/symptoms of central nervous system (CNS) infection. Patients were divided into group 1 (nine patients, IV colistin alone) and group 2 (nine patients, IV plus IVT colistin). Results: Cerebrospinal fluid sterilization was documented for 12 of 18 patients (66.6%). The CSF sterilization rate was 33.3% in group 1 and 100% in group 2 ( P  = 0.009). The mean time to CSF sterilization was 21 days (range 8–48). Five patients died due to A. baumannii CNS infection (all in group 1), and five deaths were unrelated to A. baumannii ventriculomeningitis. Intensive care unit mean length of stay was shorter in group 2 (20.7 vs. 41.6 days, P  = 0.046). Crude relative risk ratio of cumulative incidence of persistent CNS infection in group 1 versus group 2 was 13. No cases of chemical meningitis due to intrathecal colistin administration were encountered. Conclusions: Intraventricular colistin administration is much more effective than IV therapy alone and does not seem to add further toxicity.